Three-Dimensional Nanostructured Palladium with Single Diamond Architecture for Enhanced Catalytic Activity - Matthew Burton (ACS Applied Materials & Interfaces, 2018)
Fuel cells are a key new green technology that have applications in both transport and portable power generation. Carbon-supported platinum (Pt) is used as an anode and cathode electrocatalyst in low-temperature fuel cells fueled with hydrogen or low-molecular-weight alcohols. The cost of Pt and the limited world supply are significant barriers to the widespread use of these types of fuel cells. Comparatively, palladium has a 3 times higher abundance in the Earth’s crust. Here, a facile, low-temperature, and scalable synthetic route toward three-dimensional nanostructured palladium (Pd) employing electrochemical templating from inverse lyotropic lipid phases is presented. The obtained single diamond morphology Pd nanostructures exhibited excellent catalytic activity and stability toward methanol, ethanol, and glycerol oxidation compared to commercial Pd black, and the nanostructure was verified by small-angle X-ray scattering, scanning tunneling electron microscopy, and cyclic voltammetry.